Quick Analysis of The Applied Teaching Factory in The Independent Learning Curriculum Towards the Readliness of Enterpreneurship - Susilowati Susilowati; Diana Evawati; Yunus Karyanto; Rina Asmaul (Postgraduate, University of Mataram, 2024)
The intense competition in the food and beverage sector has led to increased consumptive behavior, which supports the economy. This presents a promising business opportunity for graduates of SMK Tata Culinary through Teaching Factory (TEFA) learning. This study aims to analyze the factors supporting and hindering TEFA's implementation, test its effectiveness, and describe the work readiness of students in Culinary Vocational High Schools in East Java. Using a mixed-method approach, the study sampled 6 schools from Surabaya, Sidoarjo, Ngawi, Lumajang, Tulungagung, and Magetan, with 50 culinary students from each school. Data collection included interviews, observations, and questionnaires, focusing on preparing students for entrepreneurship. Data were analyzed using one-factor ANOVA with SPSS 22. The results showed that student involvement in TEFA activities provided contextual experiences, enhancing critical thinking and problem-solving skills. In conclusion, TEFA's application in Vocational High Schools under the Independent Curriculum fosters creativity, innovation, and entrepreneurship, offering significant benefits for startups, business innovation, and job creation.